Alkali Activation of AOD Stainless Steel Slag Under Steam Curing Conditions. Issue 10 (3rd August 2015) - Salman, Muhammad; Cizer, Özlem; Pontikes, Yiannis; Snellings, Ruben; Dijkman, Jan; Sels, Bert; Vandewalle, Lucie; Blanpain, Bart; Van Balen, Koen
Abstract : Crystalline argon oxygen decarburization slag, in powdery form, was investigated for its hydration potential by alkali activation and curing at 80°C. Na‐silicate and K‐silicate of the same modulus were used as activators. Isothermal calorimetry at 80°C indicated exothermic reactions in the slag pastes. When the slag mortars were cured under steam at 80°C appreciable gain in compressive strength was measured. This was attributed to C–S–H which was detected in TG, FTIR, and 29 Si NMR analyses. Upon hydration at 90 d, the amount of crystalline phases decreased, whereas the XRD amorphous content in the slag increased. Electron microscopy showed the formation of different morphologies of reaction products depending on the alkaline activator employed. Presence of reaction rims around the crystalline phases with a major presence of Ca, Si, and O in the reacted matrix was observed in elemental maps.